Responses of Lemongrass (Cymbopogon citratus) Essential Oils Supplementation on in Vitro Rumen Fermentation Parameters in Buffalo - Singh, Ram Kumar; Dey, Avijit; Paul, Shyam Sundar; Singh, Mala; Punia, B.S. (Indian Journal of Animal Nutrition, 2018)
The present study was carried out to investigate the effect of addition of graded dose of lemon grass (Cymbopogon citrates) essential oils (LGO) on in vitro rumen digestibility and fermentation parameters in buffalo. Two separate experiments were conducted with either oats hay or a mixed feed (oats hay: concentrate mixture, 60: 40) as substrate in completely randomized design with control (without LGO) and added with LGO @ 10, 20, 40 and 80 Î¼L of LGO/40 mL of buffered rumen fluid. Incubations were carried out in 125 mL serum bottle under anaerobic conditions at 39Â°C for 24 h. Methane concentration (%) in the head space gas reduced (P<0.01) linearly with the increasing concentration of LGO irrespective of substrate. However, truly degradable dry matter (TDDM%) reduced (P<0.01) with LGO supplementation except in LGO-10 (10 Î¼L dose). Although, both the substrates behaved comparatively in methane inhibition but inhibitory effect on TDDM was more pronounced with oats hay substrate than the mixed feed. Supplementation of LGO reduced (P<0.05) ammonia-N production for both the feeds but higher reduction was evident with mixed feed substrate. However, at low level (LGO-10), no effect was observed. There was reduction in acetate production by addition of LGO except for LGO-10 for both the substrates. There was reduction (P<0.05) in A: P ratio with addition of lemon grass oils irrespective of doses and diets. It might be concluded that lemongrass essential oils have a great potential to modulate rumen fermentation towards reducing methanogenesis and ammonia nitrogen production irrespective of dietary substance. A dose of 10 Î¼L/40mL buffered rumen fluid (LGO-10) could be used to modify rumen fermentation to lower ruminal methane production without impeding feed fermentation, however, in vivo studies are required for confirmation of these results.